The formation of a giant collapse caprock sinkhole on the Barda Negra plateau basalts (Argentina): Magnetic, mineralogical and morphostructural evidences - Diaz Michelena, Marina; Kilian, Rolf; Baeza, Oscar; Rios, Francisco; Angel Rivero, Miguel; Luis Mesa, Jose; Gonzalez, Veracruz; Arlensiu Ordonez, Amanda; Langlais, Benoit; Rocca, Maximiliano C. L.; Daniel Acevedo, Rogelio (My University, 2020)
The 1.5-km-wide, 40-m-deep, crater-like structure in the 10 Ma old Barda Negra basaltic plateau in Central Argentina was discovered in the early 2000s. Based on remote sensing surveys and on its morphological characteristics, similar to those of the Barringer crater in Arizona, the structure is described to be originated by an impact. In this study we ran several fieldwork campaigns and collected and analysed samples, in order to find more evidences to endorse or reject this hypothesis. We observe a circular depression not generally surrounded by raised rims, in contrast to craters produced either by a meteorite impact or phreatomagmatic eruption (maars). Mineralogical investigations of rocks and sediments do not show high pressure and temperature minerals, such as coesite or stishovite, or any remnants of an impactite or impact melt/glass. Likewise, no textural evidences for impact-related fracturing or stress are observed. A detailed geomorphological mapping indicates a successive crater development which invokes local stepwise subsidence. Magneticmapping performed with the EU-funded NEWTON multisensor novel instrument shows a similar to 2000 nT field anomaly associated to the edges of the crater, and susceptibility measurements cast an important contrast between the basaltic rims and plateau, and the crater interior. Therefore, we propose a sink-hole origin for the crater, with a former collapse of the plateau basalts and a latter infill with sedimentary material. This hypothesis is supported by the fact that the 40 to 85 m thick and 14 to 15 Ma old carbonate-bearing Collon Cura Formation, underneath the 100 to 150 m thick basaltic plateau lava sheet, represents ideal rocks for dissolution and karst formation; remote sensing data show other nearby sinkholes (20 km westward), with extensions of 3 x 6 km and 100 m depth, which are emplaced within a cogenetic neighboring basaltic plateau with a similar underlying lithology; and the consistence of the magnetic model computed with this scheme and on measured rock remanence and susceptibilities of the structure and surroundings. These giant collapse sinkholes, up to 6 km in diameter, within caprocks of very thick plateau basalts, represent unique examples for planetary surface shaping processes which also occur on Mars and comets in areas with basalts or rigid caprocks. (c) 2020 The Author(s). Published by Elsevier B.V.
Keywords: caprock sinkhole; meteorite impact; volcanic maar; karst formation; magnetic mapping; coesite; plateau basalt